From the history of the creation of the Department of Psychiatry of the Dagestan Medical Institute (1936–1941) - S. B. Manyshev; K. B. Manysheva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The work is devoted to the history of the establishment of the Department of Psychiatry of the Dagestan Medical Institute. In the article, based on the first time archival materials introduced into the scientific circulation from the funds of the Central State Archive of the Republic of Dagestan and the archive of the Dagestan State Medical University, the organization of the psychiatric department and the clinic is highlighted. The contribution of the first employees was noted, the difficulties encountered in the first years of the department’s existence were highlighted. Also reviewed is the scientific work of the Department of Psychiatry of the Dagestan Medical University in the late 1930s.